Studi Antropometri Siswa Sekolah Dasar Negeri untuk Desain Mebel Ruang Kelas yang Ergonomis di Kecamatan Wonocolo, Surabaya - Nina Devinasari; Mariana Wibowo; Filipus Priyo Suprobo (Intra, 2019)
Nowadays, schools in Indonesia began to take part in a full day school program, where for 8 hours, students will learn and carry out their activities in the classroom in a seated position. at the same time the furniture used by students is still not in accordance with the body size of the students even though they already have SNI. This non-ergonomic furniture can have a negative impact on students bone growth later on. Therefore, furniture with the right size is needed to support the activities of the students while in school. Ergonomics is a science, art, and application of technology to balance all facilities used by human with the human itself. Through this study, it is known that the furniture used now by students in Wonocolo district Elementary School, Surabaya is still lacking in ergonomics so the size of the furniture that is currently used must be divided into three groups, namely classes 1-2, class 3-4, and grades 5-6 so that students can focus on learning and avoid disruption of bone growth. This research was conducted using quantitative methods with a descriptive approach. The body size of the children are then processed to obtain the results of percentile calculations as a measurement and design of ergonomic furniture in the Public Elementary School, Wonocolo Sub-District, Surabaya. The size and design of the furniture that is produced can be used as a reference for the further making of furniture for Public Elementary School students in Wonocolo district, Surabaya.